The RBMX gene as a candidate for the Shashi X‐linked intellectual disability syndrome. (5th December 2014) - Shashi, V.; Xie, P.; Schoch, K.; Goldstein, D.B.; Howard, T.D.; Berry, M.N.; Schwartz, C.E.; Cronin, K.; Sliwa, S.; Allen, A.; Need, A.C.
<x xml:space="preserve">Abstract</x> A novel X‐linked intellectual disability (XLID) syndrome with moderate intellectual disability and distinguishing craniofacial dysmorphisms had been previously mapped to the Xq26‐q27 interval. On whole exome sequencing in the large family originally reported with this disorder, we identified a 23 bp frameshift deletion in the RNA binding motif protein X‐linked (RBMX) gene at Xq26 in the affected males (n = 7), one carrier female, absent in unaffected males (n = 2) and in control databases (7800 exomes). The RBMX gene has not been previously causal of human disease. We examined the genic intolerance scores for the coding regions and the non‐coding regions of RBMX; the findings were indicative of RBMX being relatively intolerant to loss of function variants, a distinctive pattern seen in a subset of XLID genes. Prior expression and animal modeling studies indicate that loss of function of RBMX results in abnormal brain development. Our finding putatively adds a novel gene to the loci associated with XLID and may enable the identification of other individuals affected with this distinctive syndrome.